Linguistic Risk-Taking in Elementary School: Importance and Design of the Learning Environment (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
This qualitative study explores the influence of the learning environment on linguistic risk-taking among elementary school students. The study is divided into two phases. The first phase consists of developing practical ideas for the classroom based on a literature review. The second phase contains semi-structured expert interviews with two elementary school English teachers. The findings suggest that a positive classroom environment, feedback, and a positive attitude toward mistakes can support linguistic risk-taking. Furthermore, the proposed practical ideas, the English Experiment Corner and Tootling, may support linguistic risk-taking among young learners. Consequently, the learning environment can contribute to promoting linguistic risk-taking in elementary school.
Keywords: Linguistic Risk-Taking (LRT); Learning Environment; Elementary School; English as a Foreign Language (EFL)